A Phototheranostic Strategy to Continuously Deliver Singlet Oxygen in the Dark and Hypoxic Tumor Microenvironment. Issue 23 (4th February 2020) - Zou, Jianhua; Zhu, Jianwei; Yang, Zhen; Li, Ling; Fan, Wenpei; He, Liangcan; Tang, Wei; Deng, Liming; Mu, Jing; Ma, Yuanyuan; Cheng, Yaya; Huang, Wei; et al.
Abstract: Continuous irradiation during photodynamic therapy (PDT) inevitably induces tumor hypoxia, thereby weakening the PDT effect. In PDT‐induced hypoxia, providing singlet oxygen from stored chemical energy may enhance the cell‐killing effect and boost the therapeutic effect. Herein, we present a phototheranostic (DPPTPE@PEG‐Py NPs) prepared by using a 2‐pyridone‐based diblock polymer (PEG‐Py) to encapsulate a semiconducting, heavy‐atom‐free pyrrolopyrrolidone‐tetraphenylethylene (DPPTPE) with high singlet‐oxygen‐generation ability both in dichloromethane and water. The PEG‐Py can trap the 1 O2 generated from DPPTPE under laser irradiation and form a stable intermediate of endoperoxide, which can then release 1 O2 in the dark, hypoxic tumor microenvironment. Furthermore, fluorescence‐imaging‐guided phototherapy demonstrates that this phototheranostic could completely inhibit tumor growth with the help of laser irradiation. Abstract : Continuous photodynamic therapy : A 2‐pyridone‐based diblock polymer (PEG‐Py) was used to encapsulate the semiconducting, heavy‐atom‐free, photosensitizer pyrrolopyrrolidone‐tetraphenylethylene (DPPTPE). PEG‐Py can trap the 1 O2 generated from DPPTPE under laser irradiation and then release 1 O2 in the dark, hypoxic tumor microenvironment. As this nanoparticle can also be used for fluorescence‐guided imaging, it could be used as a phototheranostic agent.